Improving Students' Writing Skills Through the Controlled to Free Approach with Do-It-Yourself (DIY) “Daily activities” - Geroda, Godefridus Bali; Rohman, Abdul; Nur , Dedi Rahman (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
The purpose of this research is to investigate the effectiveness of a blended pedagogical approach in improving students' writing skills. This approach combines a controlled-to-free writing method with engaging Do-It-Yourself (DIY)